أثر التغيير الإلزامي للمراجع الخارجي علي جودة التقارير المالية "دليل من بيئة الأعمال السعودية" - Abdelhalim, Ahmed (مجلة العلوم الإدارية و الإقتصادية, 2019)
The objective of this research is to explore the impact of the external auditor’s mandatory change on the financial reporting quality in the Saudi business environment. Research Methodology: This study was conducted on a sample of (141) companies listed on the Saudi Stock Exchange during the period from 2012 to 2016. The researcher adopted the method of analysis of the content of financial reports. Results: The results of the applied study showed a statistically significant relationship between the external auditor’s change and the financial reporting quality. The correlations were negative between the rate of return on assets, the quality of corporate governance, the type of auditing office and the financial reporting quality. While there is no significant impact of the financial leverage and the size of the company and the type of activity on the quality of financial reports. Recommendations: Firstly, the professional and legislative entities should set the mechanisms and regulations for the external auditor’s mandatory change in a way that is suitable for the Saudi business environment. The registered company should be obliged to disclose the reasons for conflicts with external auditors within the 12 months that precedes the change. Finally, the necessity of establishing a national council under the title of “controlling council” that will have the authority of controlling, appointing, and changing auditors.